Application of cone-beam computed tomography (CBCT) for diagnosis and management of mandibular condyle fractures - Acharya, Pradip; Ren, G; Jaisani, MR; Dongol, A; Yadav, RP; Mahat, AK; Dong, F (Health Renaissance, 2017)
Background: Cone beam computed tomography (CBCT) provides precise imaging of temporomandibular joint anatomy without superimposition and distortion. CBCT is relatively a new imaging modality and used commonly in dental practice. Objective: The aim of this study is to present detailed imaging of emporomandibular joint in case of condyle fracture using CBCT for its use in diagnosis, surgical planning and evaluation of treatment. Method: In our study, we evaluated 3D - CBCT (three dimensional Cone beam computed tomography) examinations of 18 patients with mandibular condyle fractures. All of the fractures in our cases were overlooked on CBCT, thus providing axial, coronal and para-sagittal imaging of condylar head including 3D dimensional volumetric images of the condyle and surrounding structures. Result: Out of 18 condylar fracture patient’s CBCT, 8 radiographs showed condylar head (intracapsular) fracture, 2 condylar neck, 8 subcondylar fracture. 13 condylar fractures were unilateral and 5 were bilateral fracture. 9 of the condylar fractures were not associated with the mandible fracture. Out of the 9 associated condylar fractures; 3 were associated with symphysis fracture, 4 associated with parasymphysis fracture, 1 associated with body fracture and remaining 1 associated with mandibular angle fracture. 6 of the condylar fracture showed no signs of displacement of the fractured part and among 12 displaced condylar fracture parts 8 medially and 4 laterally displaced recorded in CBCT. All of the patients were given treatment on the basis of CBCT diagnosis and the results obtained from it was clinical satisfactory without complaints. Conclusion: We concluded that CBCT is the latest sophisticated technology which provides clear image of condylar head without superimposition of other structures, presented supplementary information for a more effective diagnosis and management of mandibular condyle fractures. Health Renaissance 2015;13 (3): 73-81